Modelling predictors of blog stickiness and retention by university students - Ramayah, T.; Nejati, Mehran; Shafaei, Azadeh (2015)
Weblogs represent a popular tool for sharing common knowledge and promoting learning among university students. Yet, little is known about what influences university students to stick to a blog. The current study develops a framework to investigate the role of several key factors on blog stickiness and retention among university students. Data for the study was collected from a sample of university students in Malaysia (n=725) and analysed using structural equation modelling. Results of the study revealed that social influence, content quality and perceived enjoyment were the most important predictors of blog stickiness, resulting in blog retention. More specifically, it was found that the need for cognition, perceived enjoyment and social influence also play a key role in predicting blog stickiness among student. Results of this study help to provide insights to the social, cognitive and physiological components that will encourage student to read and use blogs more frequently. This understanding can assist in designing approaches to increase blog application, stickiness and retention among students and help educate better learners capable of obtaining information from electronic sources of knowledge.